A nitrogen-doped asymmetric phenalenyl with a zwitterionic ground state. Issue 68 (2nd August 2021) - Miao, Fang; Chen, Hanjiao; Moles Quintero, Sergio; Xue, Guodong; Casado, Juan; Zheng, Yonghao
Abstract : Asymmetric azaphenalenyl radicals! A unique strategy from Blatter radicals is used to access rare asymmetric phenalenyl radicals. Abstract : Herein, an asymmetric N-doped phenalenyl (BTAP ) compound has been synthesized and carefully studied for the first time. The synthesis of BTAP reveals a planar configuration and an unexpected zwitterionic ground state with the negative charge delocalized around the circumjacent part and the positive charge mainly localized on the center.